Conctruct Validity Assessment of Dundee Ready Educational Environment Measurement (Dreem) in a School of Dentistry - Michael Andreas Leman (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Introduction: Learning environment in educational institutions of medicine and health is an important thing to be evaluated, so it takes a valid and reliable instrument. Dundee ready Educational Environment Measurement (DREEM) is one of the most frequently used instruments to evaluate the learning environment in various countries, including Indonesia. However, some psychometric study cannot prove the construct validity of DREEM. This study aims to assess the construct validity of Indonesian version of the DREEM in Study Program of Dentistry, Faculty of Medicine, University of Sam Ratulangi.Method: A total of 352 medical students were divided into three groups asked to complete the DREEM. Evaluation of the construct validity of DREEM was assessed by calculating the score of internal consistency, testing the validity of the items by Pearson Product Moment Correlation test, and confirmatory factor analysis.Results: 50 items of DREEM proven to have good reliability score (Cronbach alpha 0.883), but the two subscales have lower internal consistency score (alpha Cönbach <0.7). Seventeen items are categorized as bad items (r <0.3), the item composition is different compare to the original instrument, and there are only two items (item No. 43 and 44) in the same subscale which has strong correlation (r > 0.6).Conclusion: Indonesian translation of DREEM proved to be reliable, but the construct validity of this instrument cannot be proven in this study. It is hoped that this DREEM psychometric research continues in various countries as a basis for improving these instruments.